2019
DOI: 10.3390/polym11071139
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Fluorescence Sensing and Imaging of ATP Using a Boronic Acid Groups-Bearing Polythiophene Derivate

Abstract: A boronic acid groups-bearing polythiophene derivate (L) was designed and synthesized for highly sensitive fluorescence detection of ATP based on a multisite-binding coupled with analyte-induced aggregation strategy. L has a polythiophene backbone as fluorophores and two functional side groups, i.e., quaternary ammonium group and boronic acid group, as multibinding sites for ATP. When various structural analogues such as ADP, AMP, and various inorganic phosphates were added into the aqueous solution of L, only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…99, 104 and 106) and some of them were not able to detect ATP selectively over other important biological phosphate anions and nucleotides (ref. 23, 98, 101–103 and 105). More importantly, none of these sensing platforms were utilized to develop real-time fluorescent assays to evaluate the enzymatic activity of ALP.…”
Section: Resultsmentioning
confidence: 99%
“…99, 104 and 106) and some of them were not able to detect ATP selectively over other important biological phosphate anions and nucleotides (ref. 23, 98, 101–103 and 105). More importantly, none of these sensing platforms were utilized to develop real-time fluorescent assays to evaluate the enzymatic activity of ALP.…”
Section: Resultsmentioning
confidence: 99%
“…Complexes of multicharged ions are more interesting, since their connection to ATP is also associated with the presence of anions in the triphosphate part of ATP [7]. In addition to the electrostatic interaction, hydrophobic, 𝜋-𝜋 stacking interactions can be formed, or hydrogen bonds can appear, that is, accompanied by the complexation of ATP with more complex molecular systems, which are often used to visualize the presence of ATP [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The authors then demonstrated its application for sensing oxygen in model tumor spheroids. Zhao et al developed a fluorescence sensor for adenosine triphosphate (ATP) in aqueous solution and HeLa cells using polythiophene that bore boronic acid and quaternary ammonium moieties [12]. The boronic acid and quaternary ammonium groups in the polymer bound to the diol and phosphate groups in ATP, respectively.…”
mentioning
confidence: 99%